The Impact of Employees’ Empowerment Strategy On the Quality of Services Provided by Jordanian Islamic Insurance Companies - AL-Qadi, Naim (The Arab Journal of Administration, 2018)
This study identifies the impact of employees’ empowerment strategy in the quality of services provided by Jordanian Islamic insurance companies. The data was collected from two companies (Islamic Insurance and First Insurance). A simple random sample of size (89) was withdrawn from (241) employees. Several statistical methods such as simple regression testing, normal distribution analysis, and descriptive statistics were used. Based on the testing hypotheses and the analysis of the data collected, findings in Companies being considered in the study committed with employees’ empowerment strategy, and the quality of services provided by the following dimensions (response degree, safety degree, tangibility degree, empathy degree, and reliability degree). Also, The Employees’ empowerment strategy enables workers to contribute significantly to increase the quality of services provided to customers. Based on these finding, The necessity to work on the rehabilitation, training of employees, and enhancing their decision-making abilities to improve the quality of services provided to customers.